Murine cutaneous responses to the rocky mountain spotted fever vector, Dermacentor andersoni, feeding - Heinze, Dar M.; Carmical, J. Russ; Aronson, Judith F.; Alarcon-Chaidez, Franscisco; Wikel, Stephen; Thangamani, Saravanan (Frontiers in Microbiology, 2014)
Tick salivary glands produce complex cocktails of bioactive molecules that facilitate blood feeding and pathogen transmission by modulating host hemostasis, pain/itch responses, wound healing, and both innate and adaptive immunity. In this study, cutaneous responses at Dermacentor andersoni bite-sites were analyzed using Affymetrix mouse genome arrays and histopathology at 12, 48, 96 and 120 hours post- infestation (hpi) during primary infestations and 120hpi during secondary infestations. The microarray data suggests: (1) chemotaxis of neutrophils, monocytes, and other cell types; (2) production and scavenging of reactive oxygen species; and, (3) keratin- based wound healing responses. Histological analysis supported the microarray findings. At 12hpi, a mild inflammatory infiltrate was present in the dermis, especially concentrated at the junction between dermal connective tissue and underlying adipose tissue. A small lesion was located immediately under the hypostome and likely represents the feeding “pool.” Surprisingly, at 48hpi, the number of inflammatory cells had not increased from 12hpi, perhaps mirroring the reduction in gene expression seen at this time point. The feeding lesion is very well defined, and extravasated erythrocytes are readily evident around the hypostome. By 96hpi, the inflammatory infiltrate has increased dramatically and the feeding lesion appears to have moved deeper into the dermis. At 120hpi, most of the changes at 96hpi are intensified. The infiltrate is very dense, the epidermis is markedly thickened, the feeding lesion is poorly defined and the dermal tissue near the hypostome appears to be loosing its normal architecture. In conclusion, during D. andersoni feeding infiltration of inflammatory cells increases across time concurrent with significant changes in the epidermal and dermal compartments near the feeding tick. The importance of changes in the epidermal layer in the host response to ticks is not known, however, it is possib